A regime biting its tail: how previous semi-authoritarian structures contributed to Burkina Faso's security crisis. Issue 1 (2nd January 2023) - Hubert, Nicolas
ABSTRACT: Based on field research carried out in Burkina Faso between October 2018 and April 2019, this article interrogates the impact of Burkina Faso's long-standing political system and the distribution of authority inherited from previous regimes on the country's current political violence and conflict dynamics. The article aims to show that the country's current state of fragility and political violence do not result from regime change but rather have their roots in the country's political infrastructure. The article highlights how the disruption of patronage networks, resulting from both the overthrow of Blaise Compaoré and the 2016 municipal elections, has provided an opportunity for armed groups and criminal networks to compete against the legitimacy of Burkina Faso's central authority.